Chronic Invasive Nongranulomatous Fungal Rhinosinusitis in Immunocompetent Individuals. (15th September 2016) - Turhan, Ozge; Bostanci, Asli; Ozbudak, Irem Hicran; Turhan, Murat
Abstract : Chronic invasive nongranulomatous fungal rhinosinusitis is a well-described but uncommon type of fungal rhinosinusitis (FRS). While the prevalence of chronic FRS is 0.11% in healthy individuals, only 1.3% of them are in nongranulomatous invasive nature. The majority of the cases in the literature have been reported from developing countries mostly located in the tropical regions, as typically occurring in the background of diabetes mellitus or corticosteroid treatment. The current paper reports four consecutive cases, who were diagnosed within a short period of six months at a single center of a country located outside the tropical climate zone. None of the patients had a comorbid disease that may cause immune suppression or a history of drug use. The only risk factor that may have a role in development of chronic invasive nongranulomatous FRS was that all of our patients were people working in greenhouse farming. Three cases underwent endoscopic sinus surgery, and one case underwent surgery with both endoscopic and external approaches. Systemic antifungal therapy was initiated in all cases in the postoperative period with voriconazole 200 mg orally twice a day. All patients achieved a complete clinical remission. Chronic invasive nongranulomatous FRS should be kept in mind in the presence of long-standing nonspecific sinonasal symptoms in immunocompetent individuals, particularly with a history of working in greenhouse farming.